Tabung Haji research and development (R&D): initiating best practices - Zawawi, Dahlia; Raja Yusof, Raja Nerina (Universiti Putra Malaysia Press, 2014)
This is a case study highlighting the best practices of Lembaga Tabung Haji (TH). Among the TH pioneer initiatives discussed include the recognition by the International Organization for Standardization (ISO), the creation of pilgrim medical treatment record book (Buku Rekod Rawatan Jemaah Haji – BRRJH), and the invention of the pilgrim tracking management system. Apart from that, TH had also implemented extensive trainings for pilgrims, trainers and hajj facilitators, applied computerized system on rooms/buses/tents allocation for pilgrims, and the creation of the online ibadah and online counselling. These research and development initiatives portrayed TH’s continuous efforts in improving their services in assisting pilgrims in their Hajj journey.